Cyclin-Dependent Kinase-Dependent Phosphorylation of Sox2 at Serine 39 Regulates Neurogenesis - Lim, Shuhui (Mol Cell Biol, 2017)
Sox2 is known to be important for neuron formation, but the precise mechanism through which it activates a neurogenic program and how this differs from its well-established function in self-renewal of stem cells remain elusive. In this study, we identified a highly conserved cyclin-dependent kinase (Cdk) phosphorylation site on serine 39 (S39) in Sox2. In neural stem cells (NSCs), phosphorylation of S39 enhances the ability of Sox2 to negatively regulate neuronal differentiation, while loss of phosphorylation is necessary for chromatin retention of a truncated form of Sox2 generated during neurogenesis. We further demonstrated that nonphosphorylated cleaved Sox2 specifically induces the expression of proneural genes and promotes neurogenic commitment in vivo. Our present study sheds light on how the level of Cdk kinase activity directly regulates Sox2 to tip the balance between self-renewal and differentiation in NSCs.